PENGARUH PENGGUNAAN GAME ONLINE MOBILE LEGENDS TERHADAP EMOSIONAL SISWA - Fitria Puji Lestari; Nur Hidayah; Yunan Hidayat (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2023)
This study aims to determine whether there is an influence between the use of Mobile Legends Online Game on the Emotional Students of Class XI, XII SMA Negeri 1 Plupuh Sragen. This study uses a quantitative-correlational method. The population in this study were students of class XI, XII SMA Negeri 1 Plupuh Sragen, totaling 414 students and sample 81 students. Data collection techniques in this study used a questionnaire method. While the data analysis techniques in this study used descriptive analysis techniques which were processed using the SPSS software. The results of this study indicate that (1) the use of the Mobile Legends Online Game at Plupuh 1 Public High School as evidenced by analyzing the questionnaire with the number of respondents 81 students being in the medium category, namely 65.4%. (2) Then on Student Emotional which is proven by analyzing the questionnaire with the number of respondents 81 students are in the medium category which is 69.1%. (3) There is a very strong influence between the use of the Mobile Legends Online Game on the Emotions of Class XI, XII Students at SMA Negeri 1 Plupuh Sragen. It is known from the results of data analysis tests using simple linear regression analysis which produces a significance value of 0.025 <0.05 meaning there is a positive and significant relationship. And if it is known that the t value is 2,288 > 1,994, then the results of the hypothesis test for the strength of influence criteria between the variables of using Mobile Legends Online Games on Student Emotions have a very strong correlation or influence.